Bacteriophage Therapy: Innovations, Mechanism, and Emerging Applications in Modern Medicine (Stamford Journal of Microbiology, 2024)
Bacteriophages, viruses that specifically target and kill bacteria, are among the most prevalent organisms on Earth. This paper explores the expanding applications of bacteriophages, particularly in the context of phage therapy, where virulent phages are employed to combat bacterial infections. With the rising threat of antibiotic resistance, bacteriophages offer a promising alternative for treating bacterial diseases in humans and animals. Their use extends beyond healthcare, playing a significant role in biocontrol in health and food safety. Bacteriophages not only eliminate harmful bacteria but also contribute to the natural balance of microbial populations, influencing microbial evolution through horizontal gene transfer. Furthermore, their versatility has led to applications in biotechnology, including vaccine delivery, microbial detection, and the development of systems for protein and antibody display. The ease with which bacteriophages can be manipulated has made them valuable tools in both therapeutic and research settings. This paper also advocates for the growth of phage production companies and the use of phage cocktails, which combine multiple phages, to address diverse bacterial infections at various stages. The promising future of bacteriophage-based therapies and their potential to revolutionize the treatment of bacterial diseases is underscored throughout.Stam. J. Microbiol. 2024; 14(1): 28-35